The Influence of Salt Concentration on Peda Chub Mackerel (Rastrelliger Sp.) with Spontaneous Fermentation - . Desniar; Djoko Poernomo; Wini Wijatur (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
Peda is one of fermented fish product without further drying process, so it still classified as an intermediate moisture food where the fermentation process is still exist. The objective of research was to know the influence of salt concentration on peda spontaneous fermentation process. The treatment was immersion on salt concentrations (30%, 40%and 50%) with two salting phase. Parameters which observed were pH, water activity (aw), total viable count (TVC), lactic acid bacteria count (LAB) and salt content during 0, 6, and 14 days of fermentation. The changes of raw material and its chemical composition were also analyzed include moisture, ash, protein and lipid, while total volatile basic (TVB) and trimethylamine (TMA) were observed at the end product a long with the sensory test. During the fermentation process, the value of pH, aw, salt content and log TVC decreased, while the BAL total log increased. The proximate analyses showed that the moisture and protein on raw material were 73.91% and 22.01% respectively which higher with the product 52.71-53.94% for moisture and 20.15-21.54% for protein, while ash and lipid raw material were 3,22% and 0,22% respectively which lower from its product 1.25-1.37% for ash dan 15.96-16.90% for lipid. The content of TVB (18.42-16.78mg/ 100 gr) and TMA (3.35-2.23 mg/ 100 gr) of peda were decrease while increasing the salt content (30-50%). The sensory test indicated no significant different result in between all treatments. Therefore, the determination of selected product was based on the result of sensory test eg. 30% salt.Keywords: chub mackerel, fermenstation, peda, Rastrelliger sp